2017
DOI: 10.3151/jact.15.579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fly Ash on Mechanical Properties of PC Girder Using Reac-tive Andesite Aggregates

Abstract: In the Hokuriku region, alkali-silica reaction (ASR) caused severe degradations in many concrete bridges. However, criteria for repair and replacement works of these structures are still unclear. For the development of damage evaluation procedure, it is necessary to investigate the load-carrying capacity of prestressed concrete (PC) girders affected by ASR-induced deterioration in actuality. This study constructed two full-size PC specimens from the high-early-strength Portland cement and reactive aggregates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…Regarding the static elastic modulus, the results obtained from the water-leakage part showed that it decreased to about half of that obtained from the dry part. Previous studies pointed out that the elastic modulus was significantly degraded by the ASR-induced deterioration (Kubo et al 2006;Ha et al 2017). This outcome was also confirmed by the results on the RC slab of the test bridge.…”
Section: Compressive Strength and Static Elastic Modulussupporting
confidence: 77%
See 3 more Smart Citations
“…Regarding the static elastic modulus, the results obtained from the water-leakage part showed that it decreased to about half of that obtained from the dry part. Previous studies pointed out that the elastic modulus was significantly degraded by the ASR-induced deterioration (Kubo et al 2006;Ha et al 2017). This outcome was also confirmed by the results on the RC slab of the test bridge.…”
Section: Compressive Strength and Static Elastic Modulussupporting
confidence: 77%
“…The ASR gel increases in volume, exerting a significant pressure within the material, which causes spalling, cracking, and loss of strength in the concrete and rebar. The relationship between the characteristics of ASR-induced damage and the reduction in the elastic modulus have been proved by many previous studies (Giaccio et al 2008;Ha et al 2017). Over the years, many researchers have performed loading tests on both ASR-degraded PC and RC specimens.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations